Private digital cryptoassets as investment? Bitcoin ownership and use in Canada, 2016-2021 - Daniela Balutel; Walter Engert; Christopher Henry; Kim P. Huynh; Marcel-Christian Voia (Bank of Canada, 2022)
This report studies the dynamics of Bitcoin awareness and ownership from 2016 to 2021, using the Bank of Canada's Bitcoin Omnibus Surveys (BTCOS). In 2021, Canadians' awareness of Bitcoin remained stable at about 90%, while ownership increased to 13% from the 5% observed in 2018-2020. Canadian Bitcoin owners in 2021 were more likely to be male, aged 18 to 34 years old, with a university degree or high income. They largely see Bitcoin as an investment. A new question added to the 2021 BTCOS helps us understand the influx of investors to the Bitcoin market. Responses to this question show that roughly half of current Bitcoin owners invested during the COVID-19 pandemic (2020-2021). These recent owners differ in several ways from long-term owners. Finally, we document the broader economic context of the increase in Bitcoin ownership: widespread increases in savings and wealth by Canadian households during the pandemic, coupled with financial technology (fintech) companies providing accessible and user-friendly platforms for buying Bitcoin.
Keywords: E4; C12; O51; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods